Smart and Controllable rAAV Gene Delivery Carriers in Progenitor Cells for Human Musculoskeletal Regenerative Medicine with a Focus on the Articular Cartilage - Rey-Rico, Ana; Cucchiarini, Magali (Current Gene Therapy, 2017)
Cell therapy using mesenchymal stem cells (MSCs) is a powerful tool for the treatment of various diseases and injuries. Still, important limitations including the large amounts of cells required for application in vivo and the age-related decline in lifespan, proliferation, and potency may hinder the use of MSCs in patients. In this regard, gene therapy may offer strong approaches to optimize the use of MSCs for regenerative medicine. Diverse nonviral and viral gene vehicles have been manipulated to genetically modify MSCs, among which the highly effective and relatively safe recombinant adeno-associated viral (rAAV) vectors that emerged as the preferred gene delivery system to treat human disorders. Yet, clinical adaptation of such gene vehicles may be limited by several hurdles, including the possibility of dissemination to nontarget sites and the presence of immune and toxic responses in the host organism that may impair their therapeutic actions. The use of smart biomaterials acting as interfaces to enhance the temporal and spatial presentation of therapeutic agents in the target place and/or acting as scaffolding for MSC growth is an innovative, valuable approach to overcome these shortcomings that else restrain the efficacy of such potent cell populations. Here, we provide an overview on the most recent tissue engineering approaches based on the use of biomaterials acting as vehicles for rAAV vectors to target MSCs directly in the recipient (in vivo strategy) or as supportive matrices for rAAV-modified MSCs for indirect cell reimplantation (ex vivo strategy) as means to activate the reparative processes in tissues of the musculoskeletal system.
Keywords: Musculoskeletal system